FAMILY PSYCHOTHERAPY AND TECHNIQUES - Pulatova Gulnoza Murodilovna (Bright Mind Publishing, 2025)
This article provides information on the basic definition and content of the concept of family psychotherapy. The history of the development of systemic family psychotherapy shows that this area of practice is not as developed as most schools and approaches to psychotherapy. In this sense, modern approaches to family psychotherapy, a summary of the conducting techniques of the methods of psychotherapy used, form the main content of the article.
Keywords: Psychological Counseling, Psychotherapy, dysfunctional family, family psychotherapy, relaxation, N. Pezeshkian, rational-emotional psychotherapy.